Should I say it in English? Exploring language effects on print advertising among Latin American bilinguals. Issue 6 (2nd November 2017) - Alvarez, Cecilia M. O.; Uribe, Rodrigo; León De-La-Torre, Ricardo
ABSTRACT: Despite the extensive research conducted on language standardization in advertising across several countries, little attention has been given to the use of English versus Spanish and code-switching when advertising to Latin American bilingual consumers. We propose that stereotypes about English speakers and code-switching have potential to help determine which language is most effective in print advertising. The results of experiments conducted in Chile, Ecuador, and Mexico show that the effects of language-related stereotypes on the persuasiveness of English ads vary across different countries. In the case of Chile, English may be persuasively superior, depending on the favourableness of the stereotype of individuals that code-switch. Differently, print ads in English are functionally equivalent, in terms of ad attitudes, to Spanish and code-switching ads in Mexico, and superior in Ecuador, regardless of the favourability of the language-related stereotypes. Suggestions for advertising practice and future research are offered.